Siting Consideration for Nuclear Power Plant: A Review - Khattak, Muhammad Adil; Umairah, Aishah; Rosli, Mohamad Amirudin Mohamad; Sabri, Syeheer; Akmal Saad, Mohammad; Hamid, Mubin Solehan Abd.; Badshah, Saeed; Kazi, S. (Open Science Journal, 2017)
The purpose of this research is to study in detail about the site selection process in nuclear power plant (NPP) construction. There are various factors that contribute to the site selection which involves in-depth investigation and detailed evaluation before the site is being finalized and proposed. There are two main objectives in siting of NPP; ensuring the technical and economic feasibility of the plant and minimising potential adverse impacts on the community and environment. Geographical environment also plays an important role in siting of NPP where the source of water should be abundance. Country requirement for siting of NPP would be different for every country where they are controlled by their own regulatory bodies. About 64 published studies (1967-2017) are reviewed in this paper. It is marked from the literature survey articles that siting process is extremely crucial step in constructing NPP where public acceptance is one of the main factors, that need to be considered. Malaysia is one of the new countries embark in nuclear industry that still is in the planning phase to plan and construct its first NPP.